Molecular aspects of medicine. - Baum, Harold; Gergely, J.; Fanburg, B. L. (Pergamon Press, 1984)
Molecular Aspects of Medicine, Volume 7 discusses diseases such as urolithiasis. Another term for this disease is calculosis. Urolithiasis occurs when stones are formed in areas such as the biliary, salivary, or renal systems, but it is found more often in the urinary tract. The epidemiology and etiology of the disease are extensively covered in the book. The second chapter focuses on the cell surface of healthy and disease-infected cells. Topics such as the plasma membrane, the extracellular matrix, and cell culture and transformation are also covered in the said chapter.